Validasi bahan ajar menulis teks nonfiksi berbasis pendekatan genre - Wulan Arum Sari; Burhan Nurgiyantoro (BAHASTRA, 2020)
This research aims to describe the validity of teaching materials in writing nonfiction texts based on genre approach. The genre approach is an approach that emphasizes text types. The type of research is descriptive qualitative. The data obtained comes from the assessment of experts (lecturers), teachers, and students. The subjects in this study were three experts and five Indonesian language teachers, and 44 eighth grade students as respondents. The technique of collecting data is done by using a questionnaire. Data collection instruments include expert validation sheets, teacher assessment sheets, and student response sheets. The results of this study indicate nonfikdi text writing materials based on a genre approach based on expert velidation, teacher ratings, and student responses get a percentage score of 82.36% with good category so it can be concluded that the higher the score obtained, the better the validity results of the product.